2012
DOI: 10.3945/jn.111.153056
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Pyridoxal-5-Phosphate Is Inversely Associated with Systemic Markers of Inflammation in a Population of U.S. Adults

Abstract: Low vitamin B-6 status, based on plasma concentrations of pyridoxal-5-phosphate (PLP), has been identified in inflammatory diseases, including cardiovascular disease, rheumatoid arthritis, inflammatory bowel disease, and diabetes. Our objective was to examine the association between plasma PLP and multiple markers of inflammation in a community-based cohort [n = 2229 participants (55% women, mean age 61 ± 9 y)]. We created an overall inflammation score (IS) as the sum of standardized values of 13 individual in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
62
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 36 publications
4
62
0
Order By: Relevance
“…KTR showed positive associations with age and BMI as previously shown (33)(34)(35)(36)(37), and with neopterin, which can be explained by the fact that both neopterin and IDO are stimulated by INF-g (38)(39)(40). Both KTR and neopterin were negatively associated with PLP, which is in accordance with multiple observations of inflammation or immune activation in subject with low PLP status (41). We also observed an inverse association of KTR, and several kynurenines with cotinine, in line with published results (42), which may reflect the immunosuppressive effect from smoking (43).…”
Section: Discussionsupporting
confidence: 78%
“…KTR showed positive associations with age and BMI as previously shown (33)(34)(35)(36)(37), and with neopterin, which can be explained by the fact that both neopterin and IDO are stimulated by INF-g (38)(39)(40). Both KTR and neopterin were negatively associated with PLP, which is in accordance with multiple observations of inflammation or immune activation in subject with low PLP status (41). We also observed an inverse association of KTR, and several kynurenines with cotinine, in line with published results (42), which may reflect the immunosuppressive effect from smoking (43).…”
Section: Discussionsupporting
confidence: 78%
“…However, earlier research showed that vitamin B 6 levels are inversely associated with systemic markers of inflammation (28). In addition, mild vitamin B 6 deficiency characterizes a subclinical at-risk condition in inflammation-related diseases (29).…”
Section: Low Erythrocyte Folate Levels and Mtx Nonresponse In Ramentioning
confidence: 99%
“…There is growing evidence that vitamin B6 has anti-inflammatory activity. Epidemiological evidence indicates that patients with inflammation have significantly lower blood levels of PLP than control subjects (1,2). In patients with rheumatoid arthritis, high-dose vitamin B6 supplementation (100 mg/day) suppresses plasma IL-6 and TNF-␣ levels (3).…”
mentioning
confidence: 99%
“…The B6 vitamer pyridoxal 5Ј-phosphate (PLP) 2 is an essential cofactor for many enzymes involved in amino acid metabolism. There is growing evidence that vitamin B6 has anti-inflammatory activity.…”
mentioning
confidence: 99%